Effective Use of Public Perceptions in Assessments. (October 2019) - Lindquist, Joseph; Peng, David; Rochelle, Shawnette; Turner, Dusty; Warshaw, Matt
Over nearly two decades of war, the Department of Defense has spent tens of millions of dollars to survey the public in war-torn areas such as Iraq, Afghanistan, Philippines, Syria, and the Horn of Africa. Most often these surveys are conducted by a private polling firm, which, in turn, conducts the field work. Since field work occurs in contested or enemy-dominated terrain, direct supervision of the field work is not possible. This lack of oversight is concerning to senior leaders, who may inform decisions and assessments using this polling data. This article reviews some best practices for the expeditionary operations research system analyst when faced with the task of planning, contracting, executing, analyzing, and reporting public perception polling data in conflict affected areas. Additionally, this work codifies some of the insights uncovered during a community of practice meeting in March 2018 to include the use of latent data sources such as social media. The purpose of this effort is to provide analysts the tools to increase senior leader confidence in the data that is oft relied upon to inform operations.